1997
DOI: 10.1143/jjap.36.3944
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Transport in Single and Multiple Quantum Dots

Abstract: Ballistic quantum dots have been used in a wide variety of studies ranging from single-electron charging to chaotic systems. However, in open, ballistic quantum dots, the behavior is significantly different. Here, we discuss (1) the observation of regular, periodic fluctuations arising from the existence of stable orbits, (2) the regular and chaotic behavior of coupled dots, and (3) the theory of such dots. The regular orbit properties of these dots are their most stable, generic property, and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This is an example of a pointer state in such a dot, and this state is very long lived and clearly identified with the dot itself [21]. Moreover, it is found that this scarred state scales with the dot size [58,59]. The wave function shown in figure 2 is clearly scarred by a periodic classical orbit.…”
Section: Pointer States and Decoherencementioning
confidence: 72%
“…This is an example of a pointer state in such a dot, and this state is very long lived and clearly identified with the dot itself [21]. Moreover, it is found that this scarred state scales with the dot size [58,59]. The wave function shown in figure 2 is clearly scarred by a periodic classical orbit.…”
Section: Pointer States and Decoherencementioning
confidence: 72%
“…In paper I, we briefly discussed the scaling of the dominant frequencies, where scaling with both the dot area and with the dot edge length was observed for various dot sizes. Other studies have shown both of these behaviors [24,70]. It is clear that this scaling is supported by the density of states, with the dominant behavior depending upon which of the two terms of equation ( 15) dominates this quantity.…”
Section: Trace Formulasmentioning
confidence: 72%
“…This state is very long lived and clearly identified with the dot itself. Moreover, it is found that this scarred state scales with the dot size [53,54]. The wave function shown in Fig.…”
Section: Quantum Simulationsmentioning
confidence: 87%